Photo-degradation of high efficiency fullerene-free polymer solar cells. Issue 47 (24th November 2017) - Upama, Mushfika Baishakhi; Wright, Matthew; Mahmud, Md Arafat; Elumalai, Naveen Kumar; Mahboubi Soufiani, Arman; Wang, Dian; Xu, Cheng; Uddin, Ashraf
Abstract : Sub-bandgap defect characterization of PBDB-T:ITIC after photo-degradation by photo-thermal deflection spectroscopy (PDS). Abstract : Polymer solar cells are a promising technology for the commercialization of low cost, large scale organic solar cells. With the evolution of high efficiency (>13%) non-fullerene polymer solar cells, the stability of the cells has become a crucial parameter to be considered. Among the several degradation mechanisms of polymer solar cells, burn-in photo-degradation is relatively less studied. Herein, we present the first systematic study of photo-degradation of novel PBDB-T:ITIC fullerene-free polymer solar cells. The thermally treated and as-prepared PBDB-T:ITIC solar cells were exposed to continuous 1 sun illumination for 5 hours. The aged devices exhibited rapid losses in the short-circuit current density and fill factor. The severe short-circuit current and fill factor burn in losses were attributed to trap mediated charge recombination, as evidenced by an increase in Urbach energy for aged devices.